2018
DOI: 10.28947/hrmo.2018.19.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Colisión de aves en ventanas del Centro Universitario Victoria, Tamaulipas, México

Abstract: Las colisiones de las aves con diversas construcciones humanas (e.g., ventanales de cristal) son el segundo factor de mortalidad más importante en paisajes urbanos después de la depredación por gatos. Se ha estimado que alrededor de 988 millones de aves mueren anualmente solamente en los Estados Unidos y Canadá por estos factores. Entre agosto de 2015 y septiembre de 2016 evaluamos la frecuencia de colisiones aves-ventanas en el Centro Universitario Victoria de la Universidad Autónoma de Tamaulipas en el nores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Our knowledge regarding bird‐window collisions in Mexico is limited to two studies that list colliding birds at university buildings (Cupul‐Magaña, 2003; Gómez‐Moreno, Herrera‐Herrera, & Niño‐Maldonado, 2018) and one that assesses some ecological variables related to collisions (Gómez‐Martínez et al, 2019). In this study, we performed a citizen science survey of bird‐window collisions at seven buildings in the university campus of the National School of Higher Studies (referred to as ENES hereafter due to its acronym in Spanish) of the National Autonomous University of Mexico (referred to as UNAM hereafter due to its acronym in Spanish) located in the city of León (Guanajuato).…”
Section: Introductionmentioning
confidence: 99%
“…Our knowledge regarding bird‐window collisions in Mexico is limited to two studies that list colliding birds at university buildings (Cupul‐Magaña, 2003; Gómez‐Moreno, Herrera‐Herrera, & Niño‐Maldonado, 2018) and one that assesses some ecological variables related to collisions (Gómez‐Martínez et al, 2019). In this study, we performed a citizen science survey of bird‐window collisions at seven buildings in the university campus of the National School of Higher Studies (referred to as ENES hereafter due to its acronym in Spanish) of the National Autonomous University of Mexico (referred to as UNAM hereafter due to its acronym in Spanish) located in the city of León (Guanajuato).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, although it is still limited, there is a growing interest in studying this threat in Latin American countries. Some studies exist for Brazil 28,29 , Colombia 30–32 , Costa Rica 33–35 and Mexico 36–38 . However, there is rare or nonexistent data for other large countries with high bird diversity, such as Argentina, were around 10% of the world’s bird diversity inhabit 39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-nine of the species identified in this study have not been previously reported as affected by these structures in Mexico. These numbers suggest that power lines represent the cause of mortality affecting the widest range of bird species in the country, even greater than window collisions (71 species; Cupul-Magaña, 2003; Gómez-Martínez et al, 2019; Gómez-Moreno et al, 2018; Uribe-Morfin et al, 2021), and collision with wind turbines (29 species; Cabrera-Cruz et al, 2020; Uribe-Rivera et al, 2018). This does not mean that power lines are the main anthropogenic cause of direct bird deaths in the country, but it does reflect the enormous impact that these structures have on Mexican avifauna.…”
Section: Discussionmentioning
confidence: 99%